2017
DOI: 10.1002/anie.201701784
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of NF4+ Salts and Extraordinary Enhancement of the Oxidizing Power of Fluorine by Strong Lewis Acids

Abstract: Although the existence of the NF cation has been known for 51 years, and its formation mechanism from NF , F , and a strong Lewis acid in the presence of an activation energy source had been studied extensively, the mechanism had not been established. Experimental evidence had shown that the first step involves the generation of F atoms from F , and also that the NF cation is a key intermediate. However, it was not possible to establish whether the second step involved the reaction of a F atom with either NF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
1
9
0
3
Order By: Relevance
“…In contrast, the Seppelt structure 43 has a low PA similar to that of 1 CF 2 but has a high FA so it is Lewis acidic. Compound 43 ’s Lewis acidity is just below those of AsF 5 and SbF 5 , so it is a strong Lewis acid. In this case, the carbene carbon is not electron rich, so it wants to add a F – but does not want to strongly add a proton, consistent with its assignment as a SEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the Seppelt structure 43 has a low PA similar to that of 1 CF 2 but has a high FA so it is Lewis acidic. Compound 43 ’s Lewis acidity is just below those of AsF 5 and SbF 5 , so it is a strong Lewis acid. In this case, the carbene carbon is not electron rich, so it wants to add a F – but does not want to strongly add a proton, consistent with its assignment as a SEC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously noted that the imidazol­(in)­ylidenes have some of the highest known proton affinities . Other work on fluoride affinities has demonstrated that this reactivity can be broadly and usefully applied to inorganic reactions. …”
Section: Introductionmentioning
confidence: 99%
“…We predict that SO 3 is a stronger Lewis acid than SO 2 by approximately 35 kcal/mol at the CCSD­(T)/CBS//MP2/a­(T+d) level based on a calculated fluoride affinity of SO 3 of 90.0 kcal/mol. On the basis of the fluoride affinity of the strong Lewis acid SbF 5 (107.5 kcal/mol), we conclude that SO 3 is a moderate Lewis acid, whereas SO 2 is a much weaker Lewis acid. The experimental proton affinity of H 2 S (168.5 ± 1.3 kcal/mol) is higher than that of H 2 O (165.2 ± 0.7 kcal/mol), indicating that H 2 O is a slightly weaker Lewis base than H 2 S. These results are consistent with the higher binding energies for the SO 3 ·H 2 O/H 2 S complexes, as compared to the SO 2 ·H 2 O/H 2 S complexes.…”
Section: Resultsmentioning
confidence: 84%
“…61,62 To date, over 30 different NF 4 + salts have been prepared. 60,63 The dication systems ONF 2+ , HNNF 2+ , FNNF 2+ , H 2 NF 2+ , HNF 2 2+ , and NF 3 2+ have only been investigated by theoretical means, with Olah considering most of these systems in a GIAO-CCSD(T) study of NMR shielding. 64 The NF 2+ ion has been observed in mass spectrometry studies following ionization of NF 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For the fluoroammonium set of molecules, NF 4 + salts were first reported in 1966 independently by Tolberg, 57 Stauffer, 58 and Christe, 59,60 although not without some controversy in the race to be first. 60 Successful isolation occurred despite previous theoretical predictions that NF 4 + salts either could not be obtained or were too unstable with respect to decomposition. 61,62 To date, over 30 different NF 4 + salts have been prepared.…”
Section: Introductionmentioning
confidence: 99%